Interferência de sistemas de manejo na floresta nacional de Caxiuanã, PA nos atributos físicos e químicos na composição isotópica de solo antropizado - Silva, Rosa de Nazaré Paes da [UNESP] (2013)
The use and soil management alters soil character istics, and thus, studies related to pedology, as well as stable isotope associated with agricultural cultivation has been carried o ut over time. This study aimed to evaluate through the physical, chemical and isotopic composition of δ 13 C and δ 15 N changes caused by different tillage systems on the effective depth layer in anthropogenic soils. The experimental design was completely randomized in a 3x4 factorial design, 3 - factor use system (Terra Preta formed on Ultisol under Secondary Forest - TPI /ARGI FS ; Ultisol under Capoeira - ARGI CP and Ultisol under Plantation - ARGI RC ) and 4 - depth factor (0 to 5, 5 to 10, 10 to 20 and 20 to 30 cm) using 9 replicates. In each system was performed characterization, classification, collection and analysis of 108 composite samples. The variables studied were: particle size, carbon storage, isotopic composition of δ 13 C, δ 15 N, C and N content, C/N ratio, pH in H 2 O and ClCa 2 , soil organic matter, phosphorus, potassium, calcium, magnesium, sodium, boron, copper, manganese, iron, zinc, aluminum, hydrogen and aluminum, sum of base cation exchange capacity, capacity exchange cation effective base saturation index and the index of aluminum saturation. To evaluate the results we used the mean test (Tukey test at 5% si gnificance). It was observed that the scuffed areas C and N showed higher values at a depth of 20 to 30 cm, justifying its occurrence due to manual tilling soil litter layer incorporating deeper. Anthropogenic soils under Secondary Forest (TPI/ARGI FS ) present with low acidity and high levels of phosphorus, potassium, calcium and sodium. It is worth noting that the levels of potassium are significantly lower, which accuses the deficiency of TPI/ARGI FS for this nutrient. Significant amounts of magnesium were found in anthropogenic soil under plantation (ARGI RC) than justified by the ...